The Burglary Cognitive Distortions Scale: its association with burglary proclivity and other key variables - King-Parker, Matthew (Psychology, crime & law, 2023)
Cognitive distortions play a key role in offending but have not been researched in relation to burglary. Using the literature on offence-related cognition as a guide (which is primarily focused on sexual offending), the present two studies aimed to develop and validate the Burglary Cognitive Distortions Scale (BCDS). Drawing upon the burglary literature, an initial pool of 36-items was produced. Two online studies using community-based participants were then conducted. Each study involved administering the BCDS, along with measures of burglary proclivity, general criminal beliefs, empathy, and human needs. In Study 1 (N1 = 306), an exploratory factor analysis of the BCDS produced two factors: (1) Acquisitive Entitlement, and (2) Survive by any Means. In Study 2 (N2 = 266), confirmatory factor analysis confirmed the two-factor structure and helped refine the item pool. In each study, the 24-item CFA version of the BCDS was found to be associated with general criminal beliefs and burglary proclivity. Factor 1 of the BCDS, as well as general criminal beliefs, independently predicted proclivity scores. Future research should now aim to validate the BCDS using a sample of people who have committed burglary, as it holds promise for use in forensic settings and research.